Pandemics, Delays, and Pure Data: on 'afterlives' (2020), for Flute and Live Electronics and Visuals - Padovani, José Henrique (Revista Vórtex, 2021)
The essay addresses creative and technical aspects of the piece 'afterlives' (2020), for flute and live electronics and visuals. Composed and premiered in the context of the COVID-19 pandemic, the composition employs audiovisual processes based on different audiovisual techniques: phase-vocoders, buffer-based granulations, Ambisonics spatialization, and variable delay of video streams. The resulting sounds and images allude to typical situations of social interaction via video conferencing applications. 'Afterlives' relies on an interplay between current, almost-current, and past moments of the audiovisual streams, which dephase the performer's images and sounds. I have avoided, in text, delving deeper into the Pure Data abstractions and or into the musical analysis of my composition. The main purpose of the text is rather to present compositional/technical elements of 'afterlives' and discuss how they enable new experiences of time.